2017
DOI: 10.17219/acem/65410
|View full text |Cite
|
Sign up to set email alerts
|

Effects of vector ultrasonic system debridement and conventional instrumentation on the levels of TNF-α in gingival crevicular fluid of patients with chronic periodontitis

Abstract: Background. Tumor necrosis factor alpha (TNF-α) is an inflammatory mediator whose levels are increased in the gingival crevicular fluid and blood serum in the case of chronic periodontitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…It is well known that the goal of typical nonsurgical periodontal treatment is to remove biofilm to create the ideal environment for efficient bacterial plaque management [5,68,69]. Historically, scaling and root planing with manual instrumentation has been the most commonly used method of root surface debridement, with both clinical and microbiological benefits [70][71][72], as demonstrated by the studies included in this review [19][20][21][22][23][24][25][26][27]. Manual instrumentation also appears to be more effective in reducing the probing depth in moderate and severe periodontal pockets, according to Zhang et al, although no particular statistically significant differences were found with ultrasonic instrumentation [64].…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…It is well known that the goal of typical nonsurgical periodontal treatment is to remove biofilm to create the ideal environment for efficient bacterial plaque management [5,68,69]. Historically, scaling and root planing with manual instrumentation has been the most commonly used method of root surface debridement, with both clinical and microbiological benefits [70][71][72], as demonstrated by the studies included in this review [19][20][21][22][23][24][25][26][27]. Manual instrumentation also appears to be more effective in reducing the probing depth in moderate and severe periodontal pockets, according to Zhang et al, although no particular statistically significant differences were found with ultrasonic instrumentation [64].…”
Section: Discussionmentioning
confidence: 96%
“…According to the studies included in the review [19][20][21][22][23][24][25][26][27], there was no statistically significant differences between the treatments proposed, demonstrating the achievement of clinical outcomes with the use of ultrasonic scalers and hand instruments. These results are consistent with previous research [64][65][66][67].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations